Atopic dermatitis/Scabies. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Atopic dermatitis and scabies are very different disorders. However, these very different disorders share a symptom, namely itching. The latter can be the first symptom in both the disorders and/or can be the main problem leading the patient to the doctor. The diagnosis of atopic dermatitis is usually easy. Some difficulties are met in the first period of life, when the typical chronic and recurrent clinical course cannot be appreciated or when sites other than classical are affected. On the other hand, the diagnosis of scabies is difficult even for skilled physicians. Here we compare only the symptoms and signs more useful for the differential diagnosis.